#### Answer

x = -4
y = -2

#### Work Step by Step

3x + y = - 14
4x + 3y = -22
To the first equation solve y,after minus 3x to the both sides
3x + y - 3x = -14 - 3x
y = -14 - 3x
Substitude y = -14 - 3x to the second equation
4x + 3 ( -14 -3x ) = -22
4x - 42 - 9x = -22 use the distributive property
- 5x - 42 = -22 simplify
- 5x - 42 + 42 = -22 + 42 add 42 to the both sides
- 5x = 20
$\frac{-5x}{-5}$ =$\frac{20}{-5}$ divide both sides by -5
x = -4
substitude x for -4 to the y = -14 - 3x
y = -14 - $3\times(-4)$
y = -14 + 12
y = -2